Factors associated with body size perception among adolescent goal-oriented sports participants and non-participants: a cross-sectional Finnish study - Mäkituomas Leevi; Heikkila Laura; Nurkkala Marjukka; Korpelainen Rarija; Alanko Lauri; Heinonen Olli J; Kokko Sami; Kujala Urho; Parkkari Jari; Savonen Kai; Valtonen Maarit; Vasankari Tommi; et al. (BMC, 2025)
Background: Regardless of competitive athletes' body image pressures, only few studies have focused on adolescent sport participants' body image and the findings are inconclusive. Furthermore, the role of competitive goals in sports on adolescents' body size perception has not been studied. We examined the factors associated with adolescents' competitive goals in sports and body size perception, and the associations between adolescents' competitive goals in sports and body size perception.
Methods: The cross-sectional study consisted of 475 goal-oriented sports club participants and 936 reference youths (aged 14-16 years). The study questionnaire included multiple choice items on health behaviours, motives to exercise, competitive goals in sports and body size perception. The multinomial logistic regression analysis was used to investigate the associations.
Results: Adolescents with competitive goals in sports perceived their body size as about the right size more frequently than reference youths (68% vs 47%, p < 0.001 in girls; 74% vs 61%, p < 0.001 in boys). More than one-fourth of girls with competitive goals in sports perceived themselves as overweight, although only 7% of them were overweight. Adolescents with appearance/weight motives to exercise and poor perceived physical fitness had higher odds of perceived fatness. Additionally, BMI was positively associated with perceived fatness and negatively with perceived thinness. Having competitive goals in sports was not independently associated with perceived fatness or perceived thinness.
Conclusions: Adolescents' BMI, appearance/weight motives to exercise, and perceived physical fitness were more strongly associated with body size perception than their competitive goals in sports. However, perceived fatness among girls with competitive goals in sports should be considered in organized sports.